Absences and Silences in Critical Discourse Analysis: Methodological Reflections - Allie Slemon (International Journal of Qualitative Methods)
Critical discourse analysis (CDA) is a qualitative methodology frequently taken up by researchers to explore complex questions of how discursive power drives inequities. Across approaches to CDA, the emphasis of methodological directions has consistently been centred on examining and illuminating dominant discourses in texts. This paper argues that alongside the analysis of dominant discourses, it is crucial to examine absences and silences that are located within and beyond the text. The exploration of absences and silences can support more fulsome analysis of discourse, and is essential for challenging power structures and illuminating discourses of resistance. In this paper, three analytic strategies for attending to absences and silences in CDA are presented: (i) the lens of the theoretical framework; (ii) interrelation between dominant and excluded discourses; and (iii) positionality and local knowledges. Across each analytic strategy, an exemplar from the author’s research is presented to illustrate the practice of engaging with absences and silences in CDA research. Ultimately, this paper contends that the analysis of absences and silences can support researchers in conducting inquiry that enacts resistance to power structures that perpetuate inequities, and envisioning possible paths toward equity and justice.